2021
DOI: 10.3389/fmed.2021.662513
|View full text |Cite
|
Sign up to set email alerts
|

Ross River Virus Immune Evasion Strategies and the Relevance to Post-viral Fatigue, and Myalgic Encephalomyelitis Onset

Abstract: Ross River virus (RRV) is an endemic Australian arbovirus, and member of the Alphavirus family that also includes Chikungunya virus (CHIK). RRV is responsible for the highest prevalence of human disease cases associated with mosquito-borne transmission in Australia, and has long been a leading suspect in cases of post-viral fatigue syndromes, with extrapolation of this link to Myalgic Encephalomyelitis (ME). Research into RRV pathogenesis has revealed a number of immune evasion strategies, impressive for a vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…It is certainly tempting to speculate that SARS-CoV-2 could be added to the list of viral agents causing CFS. Lidbury et al proposed a hypothesis to explain the possible mechanisms underlying chronic post-viral fatigue syndrome; inflammatory cytokines abundantly produced during acute disease would impact on the functionality of mechanistic target of rapamycin (mTOR), a serine/threonine kinase that regulates cellular homeostasis by influencing transcription, protein synthesis, autophagy, metabolism, biogenesis, and maintenance of organelles through its signaling pathways [ 20 , 21 ]. Among its many functions, mTOR has an important role in the regulation of mitochondrial activity, oxygen consumption, and oxidative capacity, which are also based on the nutritional status and energy needs of the cell [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is certainly tempting to speculate that SARS-CoV-2 could be added to the list of viral agents causing CFS. Lidbury et al proposed a hypothesis to explain the possible mechanisms underlying chronic post-viral fatigue syndrome; inflammatory cytokines abundantly produced during acute disease would impact on the functionality of mechanistic target of rapamycin (mTOR), a serine/threonine kinase that regulates cellular homeostasis by influencing transcription, protein synthesis, autophagy, metabolism, biogenesis, and maintenance of organelles through its signaling pathways [ 20 , 21 ]. Among its many functions, mTOR has an important role in the regulation of mitochondrial activity, oxygen consumption, and oxidative capacity, which are also based on the nutritional status and energy needs of the cell [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous reports Before COVID-19, postacute syndromes were also identified after many other inflammatory pathologies such as Epstein-Barr virus, dengue fever, tick-borne encephalitis, influenza, West Nile virus, Zika virus, and Ross River virus disease. [9][10][11][12][13] In a study evaluating COVID-19 patients at 1 year after discharge, more than half of the patients had persistent fatigue and sleep disturbance. 14 In another study evaluating SARS-CoV and MERS-CoV patients who were treated in the intensive care unit and discharged, it was observed that 11%-45% of the patients continued to show limited diffusion in pulmonary function tests performed after 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Before COVID‐19, postacute syndromes were also identified after many other inflammatory pathologies such as Epstein–Barr virus, dengue fever, tick‐borne encephalitis, influenza, West Nile virus, Zika virus, and Ross River virus disease 9–13 . In a study evaluating COVID‐19 patients at 1 year after discharge, more than half of the patients had persistent fatigue and sleep disturbance 14 .…”
Section: Discussionmentioning
confidence: 99%
“…RRV has been thought to cause post-viral fatigue by evading the immune system through antibody-dependent enhancement (ADE), inflammatory cytokine dysregulation, and mitochondrial disruption. 60 ADE is a phenomenon in which preexisting antibodies facilitate viral entry into host cells rather than aiding antiviral immunity. 61 This process leads to increased virulence.…”
Section: Post-viral Fatiguementioning
confidence: 99%